2020
DOI: 10.1093/schbul/sbaa120
|View full text |Cite
|
Sign up to set email alerts
|

Implementing Precision Psychiatry: A Systematic Review of Individualized Prediction Models for Clinical Practice

Abstract: Background The impact of precision psychiatry for clinical practice has not been systematically appraised. This study aims to provide a comprehensive review of validated prediction models to estimate the individual risk of being affected with a condition (diagnostic), developing outcomes (prognostic), or responding to treatments (predictive) in mental disorders. Methods PRISMA/RIGHT/CHARMS-compliant systematic review of the W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
143
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 139 publications
(147 citation statements)
references
References 123 publications
2
143
2
Order By: Relevance
“…Moreover, health care providers and policy makers are increasingly recommending the use of prediction models within clinical practice guidelines to inform decision making at various stages of the clinical pathway. However, advances of knowledge are limited by the lack of implementation research in real-world clinical practice (82). Characterizing the long-term outcomes of psychotic disorders and identifying their baseline and clinical pathways represent crucial steps enabling risk-stratification and personalized, riskadapted treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, health care providers and policy makers are increasingly recommending the use of prediction models within clinical practice guidelines to inform decision making at various stages of the clinical pathway. However, advances of knowledge are limited by the lack of implementation research in real-world clinical practice (82). Characterizing the long-term outcomes of psychotic disorders and identifying their baseline and clinical pathways represent crucial steps enabling risk-stratification and personalized, riskadapted treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Despite these progresses, prognostic accuracy for most of these models is not sufficient to prove clinical utility and implementability across different scenarios 239 . In fact, a systematic review has found that only about 5% of the total pool of risk prediction models published in psychiatry is externally validated, and that only 0.2% are being considered for implementation (most models may not cross the implementation threshold, as they would not improve outcomes), highlighting a profound replication and translational gap 240 . For example, across all prognostic models reviewed in Table 5, only the transdiagnostic risk calculator has been piloted for real-world implementation in clinical practice 241 .…”
Section: Implementing Stratified/personalized Prognosismentioning
confidence: 99%
“…Yet, the rising demand for mental healthcare is increasingly prompting hospitals to actively work on identifying novel methods for anticipating demand and better deploying their limited resources to improve patient outcomes and decrease long-term costs 7,40 . Evaluating the technical feasibility and the clinical usefulness are inevitable steps to be made before integrating prediction models into care 28 . Along this vision, our study paves the way towards a more optimised allocation of the mental healthcare staff as well as towards an enablement of a long awaited shift in the mental health paradigm -from reactive care (delivered in the Emergency Room) to preventative care (delivered in the community).…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, little is yet known about the feasibility of querying machine learning models continuously to estimate an imminent risk of mental health crisis, which would be a key enabler for improving triage processes, for optimising healthcare staff allocation and for preventing crisis onsets. Furthermore, even a highly accurate predictive model does not guarantee the improvement of mental health outcomes and saving long-term costs 25,26 -whether predictive technologies would provide a useful tool to the practitioners in the mental healthcare practice remain unanswered to date 27,28 .…”
Section: Introductionmentioning
confidence: 99%